The Principle of Justice as a Judges' Considerations in the Concept of Third-Party Responsibility Against Cooperative Legal Action - Hariyanto, Hariyanto; Sejati, Herlambang Fadlan; Iyer, Puneet (Universitas Negeri Semarang, 2023)
This research critically examines and evaluates the judicial considerations in Supreme Court Decision Number 250 K/Pdt/2019, specifically focusing on the third parties' responsibility in connection with the Audi Et Alteram Partem principle, a pivotal aspect of the broader justice as fairness principle. Conducted as normative legal research, the study involves a qualitative analysis of data gathered through comprehensive library research. The qualitative data is systematically categorized and correlated to address the research questions accurately, facilitating a comprehensive understanding of the topic. The findings indicate that the Panel of Judges in Supreme Court Decision Number 250K/Pdt/2019, along with Decision Number 204/Pdt/2018/PT SMG and Decision Number 20/Pdt.G/2017/ PN Kds, effectively applied the Audi Et Alteram Partem principle, demonstrating a commitment to the overarching principle of justice as fairness. Notably, the panel made fair decisions while overlooking the conventional concepts of cooperatives and the responsibilities of the board of directors. The study suggests a pressing need for relevant stakeholders to promptly enact updated legislation concerning cooperatives to address emerging challenges and align with contemporary legal perspectives.